Development of the small farm: from dependency to self-reliance (FAO SantiagoCL, 1993)
Attempts to prove that in the formulation of agricultural policies overestimation of the importance and effectiveness of production factors that are external to the farms and rural communities usually occurs, as well as underestimation of the importance and effectiveness of internal factors. Suggests an edogenous development model which is more self-generated, self-managed and self-reliant, that can be effective in the solution of rural families' most urgent problems.
DC